Work-Related Stress in the Banking Sector: A Review of Incidence, Correlated Factors, and Major Consequences - Giorgi, Gabriele; Arcangeli, Giulio; Perminiene, Milda; Lorini, Chiara; Ariza-Montes, Antonio; Fiz-Perez, Javier; Di Fabio, Annamaria; Mucci, Nicola (Frontiers in Psychology, 2017)
For a number of years now, banks have been going through enormous changes in organization and structure. New technology and new ways of structuring the operation have left their mark on the working conditions and daily lives of employees. Deregulation of labor markets, emerging technologies and new types of jobs have significantly reshaping working lives by continuous changes on employment and working conditions. Such a scenario has a relevant impact not only on companies’ organization but also on working population’s health. The banking sector is particularly well-deserved of a specific and thorough analysis, in view of the recent increase in psycho-social disorders of employees. This may be related to the major organizational changes affecting this sector and, in particular, to the restructuring processes resulting from the global economic crisis. Our aim is to assess the scale of the phenomenon and how far it relates specifically to the processes of bank organization. With this in mind, through a review of the literature, we selected the main studies dealing with work-related stress in banking, so that we could reach a better understanding of the phenomenon as it relates specifically to this set of workers. The search took place on the MEDLINE® database; in total 20 articles were chosen. There was uniform agreement among the studies that stress in the banking workplace is now at critical levels, and that it can have deleterious psychological effects on workers, and on their physical health, and that organizations, too, are affected. Most studies showed that mental health problems had increased in the banking sector, and that they were stress-related. Examples began with anxiety and depression, carried on through maladaptive behaviors, and ended in job burnout. The reviewed studies’ limitations were then discussed, and possible ways forward considered.